Dental decay: from genetic to Omics (Salud, Arte y Cuidado, 2025)
Introduction: Dental caries is among the most common chronic diseases, influenced by genetic, phenotypic, and environmental factors. In recent decades, research has advanced from traditional approaches to the adoption of "omics" technologies, enabling a more detailed and personalized understanding of the disease. Objective: To review the evolution of dental caries research, from genetics to advancements in "omics" technologies, and examine how these tools are transforming caries research and treatment in a personalized manner. Methodology: A comprehensive literature search was conducted in PubMed and Scopus for studies related to dental caries, focusing on genetic research, environmental factors, and the impact of "omics" technologies (genomics, metagenomics, metabolomics, and proteomics) in the dental field. Results: Genetic factors were found to play a key role in susceptibility to caries, but the influence of environmental factors, such as diet and oral microbiota, is equally important. "Omics" technologies have enabled the identification of molecular profiles that explain variability in disease response and treatment, paving the way for personalized medicine. Advances in genomics and proteomics are facilitating more precise diagnoses and tailored treatments. Conclusion: Advances in "omics" technologies are revolutionizing the study and treatment of dental caries, providing a more comprehensive and personalized approach that integrates genetic, phenotypic, and environmental factors.
Keywords: dental caries; genetics; genomics; multiomics; integrative dentistry